1975
DOI: 10.1103/physrevb.11.4110
|View full text |Cite
|
Sign up to set email alerts
|

Paramagnetic holelike defect in irradiated calcium hydroxyapatite single crystals

Abstract: Electron-spin-resonance studies have been conducted at 9.2 and 23.1 GHz on synthetic calcium hydroxyapatite single crystals after exposure to ionizing radiation. The major paramagnetic defect is a spin-1/2 holelike center which is observable at 92 K but not at room temperature. It exhibits hyperfine interaction with a hydrogen nucleus as proved by deuterium substitution. The center is believed to be an 0 ion which results from removal of hydrogen from an OH ion. The hyper6ne interaction is w1th the hydI'ogen o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 51 publications
1
24
0
Order By: Relevance
“…Furthermore, superhyperfine interaction with a proton of a neighboring hydroxyl group has been reported (Mengeot et al, 1973(Mengeot et al, , 1974. As mentioned in the theoretical part, a reliable identification of such centers in non-model systems is not easy because of the absence of hyperfine structure and possible confusion with other oxygen radicals.…”
Section: Oxygen and Phosphate Radicals In Tooth Enamel Model Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, superhyperfine interaction with a proton of a neighboring hydroxyl group has been reported (Mengeot et al, 1973(Mengeot et al, , 1974. As mentioned in the theoretical part, a reliable identification of such centers in non-model systems is not easy because of the absence of hyperfine structure and possible confusion with other oxygen radicals.…”
Section: Oxygen and Phosphate Radicals In Tooth Enamel Model Systemsmentioning
confidence: 99%
“…Therefore, we will start our review with these two anions. (Mengeot et al, 1974), these results should be considered as highly reliable. ENDOR of CO 3 3-has also been reported in the g-range 2.0045 -2.0018 in the same type of samples (Sadlo et al, 1998b).…”
Section: Endor Studies In Enamel/apatite Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, defect centers in the anion columns of hydroxylapatite and chlorapatite have been investigated by EPR studies (Knottnerus et al 1972, Roufosse et al 1974, Mengeot et al 1975, Pan & Fleet 2002, and references herein). For example, Mengeot et al (1975) reported a spin-½ hole-like center exhibiting hyperfi ne interaction with a hydrogen nucleus (confirmed by deuteration) in X-irradiated hydroxylapatite.…”
Section: Introductionmentioning
confidence: 99%